Deep Learning applied to Learning Analytics and Educational Data Mining: A Systematic Literature Review - Coelho, Orlando Bisacchi; Silveira, Ismar Frango (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2017: Anais do XXVIII Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2017.143, 2017)
This work presents, to the extent of the authors’ knowledge, the first systematic literature review of the application of Deep Learning to Educational Data Mining and Learning Analytics. Previous literature reviews have documented several works in the areas of Educational Data Mining and Learning Analytics that used classical Artificial Neural Networks techniques. But none of them mentioned the new and much more powerful paradigm in Artificial Neural Networks: Deep Learning. This work surveys this new technique and identifies recent works in Learning Analytics and Educational Data Mining that have applied Deep Learning techniques.